(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: syphilis is a preventable and curable sexually transmitted disease, transmitted to the fetus. Although maternal treatment is easy to perform and has a low cost, Uruguay still has difficulties to control and eliminate congenital syphilis (CS). Objectives: describe the incidence of CS in Paysandú Department between 01/01/2015 and 07/31/2019. Describe epidemiological and clinical characteristics of pregnant women and their NB diagnosed with CS. Metodology: descriptive and retrospective study. The data were obtained from audits, hospitalization and clinical medical records. The CS case was defined according to the Pan American Health Organization (PAHO) and the 4 CS scenarios were described by the Centers of Design Control and Prevention (CDC). Results: there were 30 cases of CS and/or probability of CS in newborns. 27 were assisted in the Public Sector and 3 to the Private one. Almost half of them were the result of lately controlled or uncontrolled pregnancies. 37% of the mothers were illegal drug users, even during pregnancy, and in 73% cases no testing and/or treatment had been performed on their sexual partners. Conclusions: the highest prevalence of CS is observed in the public subsector. Most cases were the result of lately or poorly controlled or uncontrolled pregnancies, and came from mothers who had consumed psychoactive substances. The treatment of contacts is still an unresolved problem in the public subsector. To achieve the health objective, we must emphasize the planning, control and monitoring of pregnancies, as well as the early diagnosis and timely treatment of this infection.